2020
DOI: 10.1111/ppc.12679
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for the metabolic side effects of second‐generation antipsychotic medications: Psychiatrists' views and practices

Abstract: Purpose: The aims of this study were to explore (1) the knowledge, attitudes, practices, and adherence of psychiatrists in Jordan regarding published guidelines for metabolic monitoring of patients taking second-generation antipsychotics (SGAs), and (2) their perceived barriers to metabolic screening. Methods:The study utilized a cross-sectional survey. Data were collected from 91 psychiatrists using a self-administered questionnaire.Findings: Almost 74% of psychiatrists reported they were aware of metabolic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A cross-sectional survey conducted by Abdulhaq B showed that the financial issues and lack of compliance by the family and patients as barriers to metabolic screening [ 27 ]. However, healthcare professionals in our study recognized that their client’s ability to take healthy actions is also hampered by mental symptoms, poor cognitive functioning, physical health issues, and a lack of health information.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey conducted by Abdulhaq B showed that the financial issues and lack of compliance by the family and patients as barriers to metabolic screening [ 27 ]. However, healthcare professionals in our study recognized that their client’s ability to take healthy actions is also hampered by mental symptoms, poor cognitive functioning, physical health issues, and a lack of health information.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, concern over cardiometabolic effects and recognition of the role of mental health professionals in physical health monitoring for SMI patients have not always translated into clinical practice, with the issue having long been recognised yet continuing to recur across subspecialties and borders. [15][16][17][18][19] In the case of obesity, this has previously been attributed to lack of training and confidence around management. 20 There may also be a lack of proactiveness from healthcare professionals, with the condition going unrecognised in patients' clinical notes, clinicians underestimating the severity of patients' excess weight, clinicians lacking awareness of treatment options and having a negative attitude towards their efficacy, and the perception among clinicians that obesity arises from lifestyle choices with weight management being primarily the responsibility of the patient.…”
Section: Quality Of Carementioning
confidence: 99%